2016
DOI: 10.1007/s12288-016-0727-2
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in the Use of Granulocyte Transfusions in Neutropenic Children with Sepsis in India

Abstract: We present our data on granulocyte transfusions in children undergoing treatment for cancer and HSCT at our centre and their changing indications. In this retrospective observational analysis of children who received granulocytes from 2007 to 2015, we divided children receiving granulocytes into two groups-the first from January 2007 till December 2013 and the second from January 2014 till December 2015. This division is based on the change in our policy to use granulocytes within 48 h of septicemia as the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…The mortality or comparable outcomes such as day-28 or day-30 survival, which is reflective of the mortality related to the infection has been reported to be between 6.7 and 66.7% [2435] . There is one previous study from India in pediatric patients in which resolution of index infection was observed in 54% cases [36]. There may be several factors responsible for the wide differences reported in these studies including the dose of GTX administered, the time period in the course of infection when administered, patient populations, infection types and a low rate of patient enrolment by participating centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality or comparable outcomes such as day-28 or day-30 survival, which is reflective of the mortality related to the infection has been reported to be between 6.7 and 66.7% [2435] . There is one previous study from India in pediatric patients in which resolution of index infection was observed in 54% cases [36]. There may be several factors responsible for the wide differences reported in these studies including the dose of GTX administered, the time period in the course of infection when administered, patient populations, infection types and a low rate of patient enrolment by participating centres.…”
Section: Discussionmentioning
confidence: 99%
“…Uppuluri et al . after changing their protocol from the year 2014 onwards and administering GTX within 48 hours, showed a significant improvement in the survival from 41% to 54% (p = 0.0347) [36] . The median GTX dose/kg/IE administered by us was comparable between those who received GTX < 7 days versus those who received GTX ≥ 7 days (p = 0.851), highlighting that the benefit of early administration of GTX was not related to the GTX dose given.…”
Section: Discussionmentioning
confidence: 99%
“…5 In another study by Uppuluri et al, the early institution of granulocytes within 48 hours of a septic episode led to a statistically significant improvement in survival from 41% to 54%. 2 Garg et al in their study also found that OS was significantly higher in patients who received granulocyte transfusion (GTX) within 7 days of neutropenic sepsis (p = 0.01). 14 In our present study, due to financial constraints and unavailability of donors, granulocyte transfusions could not be initiated early within 48 hours in most of the subjects probably leading to an inferior response rate in comparison to other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Unrestricted antimicrobial use has further worsened the situation due to the development of drug resistance all over India. 2 In a surveillance study in pediatric oncology patients from a cancer center in India in Mumbai, a prevalence of communityacquired multidrug-resistant organism colonization especially due to carbapenem-resistant Enterobacteriaceae was as high as 60% and was associated with a mortality of 58-70%. 3 With the increase in incidence of drug resistance, many of these infections do not respond to treatment with appropriate antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] In our cohort, early intervention with the pediatric intensive care team in sepsis-related events, including granulocyte transfusions, has a positive impact on survival. [15] Limitations of the study include the retrospective nature, the lack of a control group and the nonavailability of MRD assessment prior to 2009.…”
Section: Discussionmentioning
confidence: 99%